Angiotensin type 1a receptors in the forebrain subfornical organ facilitate leptin-induced weight loss through brown adipose tissue thermogenesis - Colin N. Young; Donald A. Morgan; Scott D. Butler; Kamal Rahmouni; Susan B. Gurley; Thomas M. Coffman; Allyn L. Mark; Robin L. Davisson (Elsevier, 2015)
Objective: Elevations in brain angiotensin-II cause increased energy expenditure and a lean phenotype. Interestingly, the metabolic effects of increased brain angiotensin-II mimic the actions of leptin, suggesting an interaction between the two systems. Here we demonstrate that angiotensin-type 1a receptors (AT1aR) in the subfornical organ (SFO), a forebrain structure emerging as an integrative metabolic center, play a key role in the body weight-reducing effects of leptin via brown adipose tissue (BAT) thermogenesis. Methods: Cre/LoxP technology coupled with targeted viral delivery to the SFO in a mouse line bearing a conditional allele of the Agtr1a gene was utilized to determine the interaction between leptin and SFO AT1aR in metabolic regulation. Results: Selective deletion of AT1aR in the SFO attenuated leptin-induced weight loss independent of changes in food intake or locomotor activity. This was associated with diminished leptin-induced increases in core body temperature, blunted upregulation of BAT thermogenic markers, and abolishment of leptin-mediated sympathetic activation to BAT. Conclusions: These data identify a novel interaction between angiotensin-II and leptin in the control of BAT thermogenesis and body weight, and highlight a previously unrecognized role for the forebrain SFO in metabolic regulation.